Penerapan Metode Debat Terintegrasi AI Dalam Meningkatkan Kemampuan Argumentasi Peserta Didik Pada Pembelajaran Pendidikan Pancasila Di SMA Negeri 1 Garut - Nurrohimah, Annisa; Tetep (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
Argumentative ability is a higher-order thinking skill that is essential in 21st-century learning; however, in Indonesia, this ability remains relatively low. One effort that can be undertaken to address this issue is the implementation of an AI-integrated debate method. This study aims to analyze the effectiveness of the AI-integrated debate method in improving students’ argumentative skills at SMA Negeri 1 Garut, as well as to examine students’ perceptions of the implementation of this method. This research employed a quantitative approach using a quasi-experimental method with a posttest-only control group design. The research population consisted of all tenth-grade students, with class X-11 selected as the experimental group and class X-12 as the control group through purposive sampling. The research instruments included an argumentative skills posttest, observation sheets, and a student perception questionnaire. Data were analyzed using descriptive and inferential statistics. The results showed that the average score of students’ argumentative skills in the experimental class (M = 11 out of a maximum score of 16) was higher than that of the control class (M = 7). The t-test results indicated a significance value of 0.000 < 0.05, which demonstrates a significant effect of the AI-integrated debate method on improving students’ argumentative skills. In addition, the questionnaire results revealed that the majority of students expressed very good and good perceptions of the implementation of the AI-integrated debate method. Therefore, it can be concluded that the AI-integrated debate method is effective in enhancing students’ argumentative abilities